EFEKTIVITAS PELAKSANAAN MAGANG BAGI CALON NOTARIS DI KANTOR NOTARIS DI KOTA BANDA ACEH - CUT INDAH PUTI SERUNI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Notaris Dr. Suprayitno, SH, MKn2. Notaris Dr. Henry Sinaga, SH, MKn3. Notaris Dr. Tony, SH, MKn According to Law No 2/2014 on the Amendment of Law No. 30/2004 on Notarial Position, a Notary is a public official who has the authority to draw up authentic deeds and other authorities as stipulated in this law. One of the prerequisites to be a Notary is apprenticeship or having been working as a notarial employee for at least 24 (twenty four) months consecutively in a Notary’s office, or on his own effort or on the recommendation of a Notarial organization after he has passed Notarial graduate program. The objective of apprenticeship is that a Notarial candidate gets skill and knowledge his job in the future. In reality, however, apprenticeship program does not run smoothly. There are some obstacles such as lack of attendance, lack of apprentice’s participation, and lack of Notaries’ development because of confidentiality and their hectic schedule. The result used juridical empirical and descriptive analytic method by analyzing Law No. 2/2014 on the Amendment of Law No.30/2004 in Notarial Position, Regulation of INI (Indonesian Notarial Association) No. 10/Perkum/INI/2018 on Apprenticeship and Technical Manual on ALB (Apprenticeship for Extraordinary Members) of INI, supported by the result of interviews with 5 Notaries and 2 notarial candidates as apprentices. The result of the research shows that the implementation of apprenticeship is very important for notarial candidates to adjust their knowledge obtained from their Notarial Graduate Program to the practice in the field. They can also practice directly a Notary’s daily activities.Therefore, apprenticeship is very important in determining a Notary’s quality.Keywords: Notarial Apprenticeship, Effectiveness in Implementing Apprenticeship, for Notarial Candidates